Investigação otobiográfica : composição de pesquisa em educação - Yatsugafu, Rubia Helena Naspolini Coelho (2017)
This dissertation aims to propose a composition of the otobiographical investigation method, an investigative gesture created from the cross reading of Friedrich Nietzsche and Jacques Derrida, inaugurated by Monteiro in 2004. The otobiographical investigation is a method of qualitative research that proposes to listen to the life from productions realized in multiples contexts, taking as a point the formation, understood as constitution of self; the experiences (Erlebnisse) that resonate throughout this process and are made present in the form of words, gestures, understandings, meanings. To create a composition of this investigation method, it is used a research method in which genealogy and otobiographical investigation converge, the work traces the tracks traversed by the concept of otobiographical investigation in publications (theses, dissertations, and articles), from the inauguration of the use of the concept until current publications. Moreover, throughout the research, as it is required by the concept of otobiographical investigation, the investigator's experiences resonate as a hammering tone in response to the provocations of the resonances produced by the other researches.